2019
DOI: 10.1103/physrevd.100.083528
|View full text |Cite
|
Sign up to set email alerts
|

Early structure formation in primordial black hole cosmologies

Abstract: Cold dark matter (CDM) could be composed of primordial black holes (PBH) in addition to or instead of more orthodox weakly interacting massive particle dark matter (PDM). We study the formation of the first structures in such ΛPBH cosmologies using N -body simulations evolved from deep in the radiation era to redshift 99. When PBH are only a small component of the CDM, they are clothed by PDM to form isolated halos. On the other hand, when PBH make most of the CDM, halos can also grow via clustering of many PB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
156
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 103 publications
10
156
0
Order By: Relevance
“…Some of the uncertainty in the precise formation mechanism is bracketed by the cases S = 1 and the full expressions of Equations ( 8) and (9). More precise numerical simulations of PBH binary formation and evolution will be required for a more quantitative investigation of the sensitivity of our results to the formation model [15,[52][53][54][55].…”
Section: A Pbh Merger Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the uncertainty in the precise formation mechanism is bracketed by the cases S = 1 and the full expressions of Equations ( 8) and (9). More precise numerical simulations of PBH binary formation and evolution will be required for a more quantitative investigation of the sensitivity of our results to the formation model [15,[52][53][54][55].…”
Section: A Pbh Merger Modelsmentioning
confidence: 99%
“…Ref. [48] showed that the DM halo which forms around PBHs [52,57] has minimal impact on the merger rate and the estimate of f PBH . Accretion onto a PBH can increase the initially negligible spin of a PBH, provided that the PBH mass grows significantly [41].…”
Section: A Pbh Merger Modelsmentioning
confidence: 99%
“…These small-scale effects include large PBH velocity dispersion, accretion, and clustering effects seen in previous numerical investigations (e.g. Hütsi et al (2019); Inman & Ali-Haïmoud (2019)). These effects will weaken the validity of the upper bounds on f pbh at such small scales.…”
Section: Observational Constraintsmentioning
confidence: 79%
“…However, if large non-Gaussian curvature perturbation were created at the relevant small scales (not probed by CMB anisotropies), the above bound could become much milder [228]. In this case, PBH clusters would be expected (e.g., [229]), which could furthermore lead to anisotropic distortion signals. Future measurements of CMB spectral distortions could shed further light on these scenarios.…”
Section: Primordial Black Holesmentioning
confidence: 99%